2017
DOI: 10.1016/j.omtm.2017.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Immune Modulatory Cell Therapy for Hemophilia B Based on CD20-Targeted Lentiviral Gene Transfer to Primary B Cells

Abstract: Gene-modified B cells expressing immunoglobulin G (IgG) fusion proteins have been shown to induce tolerance in several autoimmune and other disease models. However, lack of a vector suitable for gene transfer to human B cells has been an obstacle for translation of this approach. To overcome this hurdle, we developed an IgG-human factor IX (hFIX) lentiviral fusion construct that was targeted to specifically transduce cells expressing human CD20 (hCD20). Receptor-specific retargeting by mutating envelope glycop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 43 publications
(77 reference statements)
0
10
0
Order By: Relevance
“… 28 , 81 , 82 The possibility to use novel pseudotyping glycoproteins makes it possible to confine delivery of our chimeric Gag.MS2 particles to specific cell types, as described for retroviral targeting strategies by Buchholz and co-workers. 83 , 84 , 85 Calculation of amounts of Cas9 (in either mRNA or protein form) and guide RNA administered for gene editing in recently published articles led to estimates in the range of 1–15 pg mRNA/cell (i.e., 4.2 × 10 5 –6.3 × 10 6 mRNA molecules/cell), 5–75 pg Cas9 protein/cell (i.e., 1.8 × 10 7 –2.8 × 10 8 protein molecules/cell), and 1–100 pg guide RNA/cell (i.e., 1.9 × 10 7 –1.9 × 10 10 guide RNA molecules/cell). 21 , 22 , 25 , 68 , 86 Based on data presented in Table 1 and an average RFP657 knockout efficiency of 44%–56%, we calculated that 9.6 × 10 2 –3.8 × 10 3 SpCas9.TS mRNA molecules/cell and 7.1 × 10 4 –5.8 × 10 5 sgRNAs/cell were delivered (to 1 × 10 5 cells with 50 μL of our 100-fold concentrated Gag.MS2 particles).…”
Section: Discussionmentioning
confidence: 99%
“… 28 , 81 , 82 The possibility to use novel pseudotyping glycoproteins makes it possible to confine delivery of our chimeric Gag.MS2 particles to specific cell types, as described for retroviral targeting strategies by Buchholz and co-workers. 83 , 84 , 85 Calculation of amounts of Cas9 (in either mRNA or protein form) and guide RNA administered for gene editing in recently published articles led to estimates in the range of 1–15 pg mRNA/cell (i.e., 4.2 × 10 5 –6.3 × 10 6 mRNA molecules/cell), 5–75 pg Cas9 protein/cell (i.e., 1.8 × 10 7 –2.8 × 10 8 protein molecules/cell), and 1–100 pg guide RNA/cell (i.e., 1.9 × 10 7 –1.9 × 10 10 guide RNA molecules/cell). 21 , 22 , 25 , 68 , 86 Based on data presented in Table 1 and an average RFP657 knockout efficiency of 44%–56%, we calculated that 9.6 × 10 2 –3.8 × 10 3 SpCas9.TS mRNA molecules/cell and 7.1 × 10 4 –5.8 × 10 5 sgRNAs/cell were delivered (to 1 × 10 5 cells with 50 μL of our 100-fold concentrated Gag.MS2 particles).…”
Section: Discussionmentioning
confidence: 99%
“…Important progress toward clinical translation of the CD20-targeted MV-LV was recently achieved by Wang and colleagues. 87 In this interesting study, B cells were isolated from human CD20-transgenic BALB/c mice and used as target cells for genetic modification by CD20-MV-LV to induce tolerance in a mouse model of hemophilia B. Astonishingly, the authors could show that CD20-MV-LV successfully transduced CD20 + mouse B cells, but not CD20 − cells, at similar efficiency as human primary B cells even without prior activation. To evaluate the clinical potential, CD20-transgenic mouse B cells were ex vivo transduced with CD20-MV-LV encoding human FIX, followed by adoptive transfer into recipient mice.…”
Section: Main Textmentioning
confidence: 99%
“…However, B cells also play a role in antigen presentation ( 64 ). Interestingly, gene-modified primary B cells have the capacity to induce immune tolerance upon retroviral or lentiviral gene transfer (while TLR9 activation during plasmid gene transfer generates immunogenic B cells) ( 65 67 ). Skupsky et al showed that the expression of IgG fusion proteins (IgG-A2 and IgG-C2 domains of FVIII) in primary B cells is a particularly powerful tool to induce tolerance ( 65 ).…”
Section: Directly Targeting B Cells For Tolerancementioning
confidence: 99%
“…A major limitation of this approach had been a lack of suitable gene transfer vectors for human B cells. Recent development of lentiviral vectors (LV) targeted to human CD20 through inclusion of a single chain antibody fragment in the viral envelope protein has overcome this bottle neck ( 67 ). Primary B cells transduced with such a LV to express IgG-FIX prevented inhibitor formation in hemophilia B mice ( 67 ).…”
Section: Directly Targeting B Cells For Tolerancementioning
confidence: 99%
See 1 more Smart Citation